ANALISIS OF PROVIDING EFFECTIVE MEDICAL AID IN PATIENTS WITH UNCOMPLICATED UNHOSPITALIZED HYPERTENSIVE CRISES IN KRASNODAR - A. S. BAGDASAR’YAN; A. A. SIRUNYANC; D. V. PUHNYAK; Zh. A. KAMALYAN; E. V. GERASCHENKO; A. S. STARITSKY (Кубанский научный медицинский вестник, 2017)
Aim. Retrospective analyses of organization and effective providing medical aid to patients with uncomplicated unhospitalized hypertensive crises (300 cases) is made according to informational base of complex automatic system under the control of Krasnodar Medical Emergency service.Material and Methods. Drugs with various activities such as captopril, moxonidine, nifedipine, urapidil, propranolol were used as hypertensive agents. Hypotensive effect was estimated every 15 to 30 minutes according to the level of systolic and diastolic blood pressure decreasing, heart rate falls and improvement of common condition. Results. Moxonidine and urapidil proved to have the most evident hypertensive properties. When the Medical Emergency service goes for a call about hypertensive crisis, it is recommended to use as antihypertensives moxonidine and urapidil in individua ldoses.Conclusion. However, the time spent on calls doesn’t allow full control for the rate of blood pressure decreasing in the course of several hours. The creation of unified emergency aid informative base with outpatient-clinical net makes it possible to observe the patients under control in the emergency aid departments and to improve succession in various stages of providing medical aid.